Studi Komparatif: Problematika Pembiayaan KPR Pada Akad Murabahah Bil Wakalah Dan Akad Musyarakah Mutanaqisah di Perbankan Syariah - Hilwa Fitri Millenia; Anita Mauliyanti; Arfarizan Arfarizan (Kafalah: Jurnal Ekonomi, Manajemen, dan Keuangan Syariah, 2026)
The goal of this research to determine the comparison of the implementation of murabahah bil wakalah and musyarakah mutanaqisah contracts in mortgage financing products at Islamic banks. Especially in responding to the existence of three issues attached to the implementation of the contract (sharia issues, legal issues, and operational issues). In its development, these two products underwent modifications with the addition of contracts so that they were considered to deviate from the original contract concept. The research method used is descriptive qualitative method with inductive analysis approach. The analysis is based on the DSN-MUI Fatwa regarding murabahah bil wakalah and musyarakah mutanaqishah, the Law of the Republic of Indonesia Number 21 of 2008 concerning Islamic Banking and other related regulations, and the Murabahah bil Wakalah and Musyarakah Muanaqisah Agreements. The result of the research is that the murabahah financing contract by including the wakalah contract can reduce the substance and shariah of the murabahah because it contradicts the DSN Fatwa Number 04/DSN-MUI/IV/2000, as well as musyarakah mutanaqisah based on shariah compliance in the DSN Fatwa No.73/DSN-MUI/ XI/2008 found a discrepancy in sharia.